Smartphones and the news - Duff, Andrew (Freelance journalist) (New York : Routledge, 2020)
"This book reviews recent studies into smartphones and the news, and argues that the greatest impact on news of the smartphone as a dominant technological artefact is to shift it away from an authoritative, fixed 'first draft of history' to become a fluid, flexible stream of information from which each individual constructs their own meaning. The news has taken on a new life, fragmented by five billion smartphones, disrupting not just an industry but also the consequence of the news in societies worldwide. This book considers how the smartphone has changed the production of journalism through contributions from the general public, the dominance of visual over textual media, the shift towards brevity, the challenges of verification, and the possibilities offered by the multi-skilled mobile journalist, or MoJo. The book looks at the manner in which news is promoted and distributed via smartphones, specifically its place on social media. Finally, it considers how news-on-smartphones fits into consumers' lives, and how their use of the smartphone to access news is impacting back on its production. This is an insightful research text for journalism students and scholars with an interest in digital journalism, new media, and the intersection between technology and communication"--
Includes bibliographical references and index.
Keywords: Online journalism; DIgital media; Citizen journalism; Journalism -- Technological innovations; Social media